Analisis Rasio Profitabilitas Dalam Menilai Kinerja Keuangan Perusahaan Pada Pt. Aneka Tambang Tbk - Luthfi Ismayeni; Nugraha, Maulana; Suryani (Jurnal Akuntansi UMMI, 2021)
This study aims to find out and analyze the financial performance of PT Aneka Tambang Tbk as seen from the financial ratio in the form of profitability ratio. The research method used is descriptive quantitative. The data used is secondary data derived from the financial statements of PT Aneka Tambang Tbk for the period 2016 to 2019.  The data analysis showed an average four-year operating profit margin ratio of 3.48%. Analysis of the ratio of gross profit margin for four years of 13.57%. The four-year ROE analysis averaged 2.75%. Analysis of the average basic earning ratio produced is 2.17% . The resulting average ROA analysis is 1.60% . And for the analysis of the ratio of employee ability to average profit generated by 193.95%. It can be concluded that the financial performance of PT Aneka Tambang Tbk is in a bad condition, this is due to a decrease in profitability ratio.